The Character of Rip van Winkle: Representation of Disappearing Cultural Identity - Magdalena Baga (Jambura Journal of English Teaching and Literature, 2020)
Abstract ─ The purpose of this research is to explore how an ethnicity is represented in a story that has a historical setting and how this ethnic group was placed in American history. The short story of Washington Irving, "Rip Van Winkle", published in 1819, was very popular in America. This story was recycled in the form of stories for children, made into plays, etc. What Americans always remember about Rip Van Winkle character is his laziness. The story of "Rip Van Winkle" is traced through Stuart Hall's Representation theory. This theory states that representation can give meaning to an identity, and the New Historicism method is used to uncover that fictional stories are tied to the world that produced them. The result shows that Rip's character is a representation of Dutch ethnicity who felt losing their cultural identity. Rip's character in the story is a representation of Dutch New York ethnicity, and he was the main character in the story who was narrated as a lazy man. Thus, what always presents in America's memory is the lazy Dutch because of the representation of the character of Rip, but the other characters who were narrated less in the story are not remembered, even though they played a role in establishing America.